Pengaruh Strategi Reading Guide terhadap Prestasi Belajar Siswa Madrasah Tsanawiyah - Manshur, Ahmad; Aziz, Su'udin; Qomariyah, Nurul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of the study was to describe the use of reading guide strategies in Akidah Akhlak subjects, Learning achievement in Aqidah Akhlak subjects. The effect of reading guide strategies on learning achievement in Aqidah Akhlak subjects. This study uses a quantitative approach. The population in this study was all eighth-grade students. Considering that the population in this study was less than 100 people, the researchers took 100% of the population. So this research is a population study. In this study, data were collected using interviews to determine the use of reading guide strategies, questionnaires to determine the effect of reading guide strategies, and using report cards to determine learning achievement. The result of this research is that there is an influence of the reading guide strategy on the learning achievement of Aqidah Akhlak, the result is 0.590 where the significance value is greater than the "r" table, both at the 5% significance level and at the 1% significance level.